A stitch in time saves nine? A repeated cross-sectional case study on the implementation of the intersectoral community approach Youth At a Healthy Weight. (December 2015) - van der Kleij, Rianne; Crone, Mathilde R; Paulussen, Theo; van de Gaar, Vivan; Reis, Ria
Abstract Background The implementation of programs complex in design, such as the intersectoral community approach Youth At a Healthy Weight (JOGG), often deviates from their application as intended. There is limited knowledge of their implementation processes, making it difficult to formulate sound implementation strategies. Methods For two years, we performed a repeated cross-sectional case study on the implementation of a JOGG fruit and water campaign targeting children age 0–12. Semi-structured observations, interviews, field notes and professionals' logs entries were used to evaluate implementation process. Data was analyzed via a framework approach; within-case and cross-case displays were formulated and key determinants identified. Principles from Qualitative Comparative Analysis (QCA) were used to identify causal configurations of determinants per sector and implementation phase. Results Implementation completeness differed, but was highest in the educational and health care sector, and higher for key than additional activities. Determinants and causal configurations of determinants were mostly sector- and implementation phase specific. High campaign ownership and possibilities for campaign adaptation were most frequently mentioned as facilitators. A lack of reinforcement strategies, low priority for campaign use and incompatibility of own goals with campaign goals were most often indicated as barriers. Discussion We advise multiple 'stitches in time'; tailoring implementation strategies to specific implementation phases and sectors using both the results from this study and a mutual adaptation strategy in which professionals are involved in the development of implementation strategies. Conclusion The results of this study show that the implementation process of IACOs is complex and sustainable implementation is difficult to achieve. Moreover, this study reveals that the implementation process is influenced by predominantly sector and implementation phase specific (causal configurations of) determinants.